2018
DOI: 10.1111/nyas.13671
|View full text |Cite
|
Sign up to set email alerts
|

Predictive rhythmic tapping to isochronous and tempo changing metronomes in the nonhuman primate

Abstract: Beat entrainment is the ability to entrain one's movements to a perceived periodic stimulus, such as a metronome or a pulse in music. Humans have a capacity to predictively respond to a periodic pulse and to dynamically adjust their movement timing to match the varying music tempos. Previous studies have shown that monkeys share some of the human capabilities for rhythmic entrainment, such as tapping regularly at the period of isochronous stimuli. However, it is still unknown whether monkeys can predictively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 69 publications
(184 reference statements)
5
90
0
1
Order By: Relevance
“…We found a strong correlation between the duration of the produced intervals and the curvilinear amplitude of the MPC neural trajectories during the SCT and ST and, due to the simultaneity of the recordings in the latter task, we decoded accurately the produced durations on a trial by trial basis. In addition, the cyclic and smooth nature of the neural trajectories during ST and SCT sharply contrasts with the tapping kinematics, which are characterized by stereotypic tapping movements separated by a dwell period that increases with the timed interval [24,25]. Previous studies have demonstrated that cell populations in premotor and motor cortical areas show rotatory non-muscle like trajectories that reflect the internal dynamics needed for controlling reaching and cycling [29,30].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…We found a strong correlation between the duration of the produced intervals and the curvilinear amplitude of the MPC neural trajectories during the SCT and ST and, due to the simultaneity of the recordings in the latter task, we decoded accurately the produced durations on a trial by trial basis. In addition, the cyclic and smooth nature of the neural trajectories during ST and SCT sharply contrasts with the tapping kinematics, which are characterized by stereotypic tapping movements separated by a dwell period that increases with the timed interval [24,25]. Previous studies have demonstrated that cell populations in premotor and motor cortical areas show rotatory non-muscle like trajectories that reflect the internal dynamics needed for controlling reaching and cycling [29,30].…”
Section: Discussionmentioning
confidence: 98%
“…The network state trajectories showed the following properties: they were simple, periodic, exhibited an amplitude modulation according to the timed duration, and were different from the stereotypic kinematics of the phasic tapping movements and the timing control of the dwell between movements in this task [24,25]. Notably, the increases in trajectory amplitude as a function of target interval were observed during the two rhythmic tapping tasks, reproduced with dPCA, and closely related with the monkeys' produced intervals during SCT and ST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in nonhuman primates have led to mixed results regarding the ability of nonhuman primates in distinguishing and perceiving different aspects of musicality, namely its pitch, harmony, and rhythmic elements. Monkeys exhibit abilities foundational to music perception such as perceiving acoustic patterns (Honing, Bouwer, Prado, & Merchant, ; Honing, Merchant, Háden, Prado, & Bartolo, ; Selezneva et al, ) as well as rhythmic entrainment (Gámez et al, ; Takeya, Kameda, Patel, & Tanaka, ). In a study with new world monkeys, tamarins and marmosets were allowed to retrieve reward from two different arms of a Y maze, which were associated with two types of music (slow tempo: 65 bpm; fast tempo: 369 bpm).…”
Section: Introductionmentioning
confidence: 99%